Individual and dialect differences in perceiving multiple cues: A tonal register contrast in two Chinese Wu dialects. Issue 1 (21st August 2020) - Jiang, Bing'er; Clayards, Meghan; Sonderegger, Morgan
This study investigates how multiple cues contribute to multi-dimensional phonological contrasts at both the group level and the individual level, and how dialectal experience shapes listeners' perceptual strategies. We examine a tonal register contrast in two Chinese Wu dialects signaled by three cues: pitch height, voice quality, and pitch contour. We found that 1) at the group level, cue weights are context-specific, i.e., vary by tone, and some contrasts rely more heavily on multiple cues than others; 2) dialectal experience affects listeners' perceptual strategy: Shanghai listeners, with their own dialect having a smaller voice quality distinction, do not rely more on the cue even when listening to stimuli with a clear breathy-modal distinction, comparing to Jiashan listeners; 3) individuals' cue weights are correlated in a positive manner, meaning that some listeners show overall larger cue weights than others; larger variability is found when the contrast has more than one salient cue, in which case individuals have different options of choosing one cue over another as the primary cue and this can work against the positive correlation.